Efficient Capsid Antigen Presentation From Adeno-Associated Virus Empty Virions In Vivo - Pei, Xiaolei; Earley, Lauriel Freya; He, Yi; Chen, Xiaojing; Hall, Nikita Elexa; Samulski, Richard Jude; Li, Chengwen (Frontiers in Immunology, 2018)
Adeno-associated virus (AAV) vectors have been successfully applied in clinical trials for hemophilic patients. Although promising, the clinical results suggest that the capsid-specific CD8+ T cell response has a negative effect on therapeutic success. In an in vitro analysis using an engineered AAV virus carrying immune-dominant SIINFEKL peptide in the capsid backbone, we have previously demonstrated that capsid antigen presentation from full (genome containing) AAV capsids requires endosome escape and is proteasome dependent and that no capsid antigen presentation is induced from empty virions. In the current study, we examined capsid antigen presentation from the administration of empty virions in animal models. In wild-type mice, similar to AAV full particles, capsid antigen presentation from AAV empty virion infection was dose-dependent, and the kinetics studies showed that antigen presentation was detected from 2 to 40 days after AAV empty virion administration. In the transporter associated with antigen processing 1 deficient (TAP-/-) mice, capsid antigen presentation was inhibited from both AAV full and empty virions, but higher inhibition was achieved from AAV full particle administration than that from empty virions. This indicates that the pathway of capsid antigen presentation from AAV transduction is dependent on proteasome-mediated degradation of AAV capsids (mainly for full particles) and that the endosomal pathway may also play a role in antigen presentation from empty particles, but not full virions. The capsid antigen presentation efficiency from AAV preparations was positively correlated to the number of empty virions contaminated with full particles. Collectively, the results indicate that contamination of AAV empty virions induces efficient antigen presentation in vivo and the mechanism of capsid antigen presentation from empty virions involves both endosomal and proteasomal pathways. The elucidation of capsid antigen presentation from AAV empty virions may allow us to rationally design effective strategies to prevent elimination of AAV transduced target cells by capsid-specific CD8+ T cells.